Analisis Strategi Pemasaran Menggunakan Bauran Pemasaran 4P Pada UMKM D’clup Chicken Crispy - Yin Yin Anomari; Elisa Simamora Simamora; Dede Putri Nur Mayati; Filbert Filbert; Naomi Sianturi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the marketing strategies implemented by the MSME D’Clup Chicken Crispy based on field observations and direct interviews with the business actors. Marketing strategy is one of the important factors in increasing the competitiveness of MSMEs amid increasingly intense competition in the culinary industry. The research method used is a qualitative method with a descriptive approach. The research data were obtained through direct observation at the business location, semi-structured interviews with the owner and employees, and supporting documentation. The results show that D’Clup Chicken Crispy’s marketing strategy applies the 4P marketing mix concept, namely product, price, place, and promotion. From the product aspect, D’Clup Chicken Crispy offers crispy fried chicken with a taste that matches consumer preferences. From the price aspect, pricing is set at an affordable level to reach various segments. From the place aspect, the business location is considered quite strategic and easily accessible to consumers. Meanwhile, from the promotion aspect, D’Clup Chicken Crispy still relies on simple promotion through social media and word-of-mouth communication. The conclusion of the study indicates that the marketing strategy implemented has been quite effective in attracting consumer interest; however, further development of more innovative promotional strategies is still needed to enhance the business’s competitiveness.